Kontribusi Pengalaman Praktik Industri terhadap Motivasi Belajar Siswa Kelas XII Teknik Pemesinan SMKS Dhuafa Padang - Muhammad Fahrozi; Waskito Waskito (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This study aims to determine the contribution of industrial work practice (Prakerin) experience to the learning motivation of 12th-grade students in the Mechanical Engineering Department at SMKS Dhuafa Padang. A quantitative correlational research approach was employed, using a questionnaire distributed to 30 students who had participated in the Prakerin program. The results indicate a strong and significant relationship between Prakerin experience and learning motivation, with a Pearson correlation coefficient of 0.763 (Sig. < 0.001). Simple linear regression analysis shows that industrial practice experience contributes 58.3% to students' learning motivation. These findings suggest that relevant and meaningful implementation of Prakerin can encourage students to become more motivated in their academic activities at school.